PUBLISHING BUSINESS MODEL IN THE 19TH CENTURY LITHUANIA : PROFESSIONAL PUBLISHER’S VIEW - NAVICKIENĖ, AUŠRA (Knygotyra, 2014)
In 1818 Józef Zawadzki compiled a systemic work of two parts about publishing business, which today as a manuscript is kept in the Warsaw University Library. In Polish and Lithuanian historiography, it is usually viewed as a set of recommendations to the politicians of the time, as well as an outline of measures designed to improve Zawadzki’s personal business. At the same time, Zawadzki’s text can also be considered as one of the first of the limited number of attempts in Central and East Europe to theorize a traditional book publishing model. As such, the document can be considered as of equal importance to the writings of progressive authors of the time such as Russian historian Nikolay Karamzin, the German book trader Friedrich Perthies and others, who discussed the peculiarities of the private publishing business. From today’s perspective the most important thing is that Zawadzki disseminated business ideas based on the free market economy and formulated a model of the publishing business. This model was based not on traditional forms of sponsorship that existed till then, but on sponsorship by society, i.e. readers who became capable of paying for the work of the authors, publishers, printers and book traders. Zawadski considered the activities of book publishing, production and distribution, which at that time were dominated by Catholic Church [confessional] institutions, were ineffective and did not correspond to the needs of the time. Therefore, he emphasised the importance of private capital and planned long-range strategies to use it. His innovative proposals for solving the rights issues of authors at the level of governance were to legitimise new mutually beneficial relationships between publishers and authors and to pass laws that would promote fair competition (the documents and activities of Zawadzki contributed to introduction of laws on copyright in East Europe and Russia, these laws emerging in 1830 as a part of censorship laws). Zawadzki’s considerations about the uniting of book workers into organisations, which would not only stimulate cooperation but also protect their rights, were also innovative. Such professional organisation was not established in Lithuania at that time, but a decade later it emerged in Germany as the Börsenverein der Deutschen Buchhandler zu Leipzig (the Association of German Book Sellers established in Leipzig in 1825) and its activity proved to be efficient. Zawadzki’s model of the publishing business corresponded to the needs of the time. As a publishing practice it had already existed in Germany and France for more than a hundred years and the private companies involved were, by that time, being run by the sons or grandsons of their founders. The first generation of professional book workers started their activities in Lithuania and Poland at the beginning of the 19th century and rapidly became the dominant means. Professional publishers in this region became established as most important arrangers of publishing and their publications were responsible for the major proportion of the publishing production. Publishing itself became an independent area of commerce and business. With the creation of publishing as a profession in itself, a new force appeared in the book industry – the publisher acting as a key player responding to developing patterns and the changing needs of the society at the time. Thus, as can be seen, the model introduced by J. Zawadzki is very much the template still in existence today, the very core of the traditional book publishing enterprise.